Turbulent Flow Structure in a Hemicylindrical Dimple on the Wall of a Flat Channel - Terekhov, V. I.; Chokhar, I. A.; Lun, N. Yan (Journal of applied mechanics and technical physics, 2025)
This paper presents the results of an experimental study of the flow structure in a hemicylindrical dimple located on one of the walls of a rectangular channel with a height m and a length-to-width ratio of 7.5. A dimple with a width m and a length calibers could be oriented at different angles to the longitudinal axis of the channel ( –90°). In the experiments, the pressure in the median sections along and across the dimple, the velocity components, and their fluctuations in the longitudinal and transverse directions were measured. In the experiments, the Reynolds number based on the flow-rate-averaged velocity and the hydraulic diameter of the channel was constant and equal to . The pressure distributions on the dimple wall both in the transverse direction and along its length were found to depend significantly on its inclination angle to the channel axis. At the dimple inlet where the flow enters, a zone of strong rarefaction was formed. The length of this zone along the dimple did not exceed one caliber, and outside this zone, the pressure coefficient remained practically unchanged up to the dimple outlet, where there was a sharp increase in pressure due to stagnation. The greatest rarefaction in the transverse direction relative to the dimple occurred at an inclination angle . The flow structure in different sections along the dimple length was studied. The maximum velocity of the circulation flow in the hemicylindrical dimple was observed at its inlet. Downstream along the dimple, the intensity of the vortex flow of the gas significantly decreased, and in the case of shallow dimples ( ), the flow became unseparated.